2020
DOI: 10.1007/s11136-020-02649-5
|View full text |Cite
|
Sign up to set email alerts
|

Developing dimensions for a new preference-based quality of life instrument for older people receiving aged care services in the community

Abstract: Purpose To identify the salient quality of life characteristics relevant to older people in receipt of community aged care services in order to develop dimensions for a draft descriptive system for a new preference-based quality of life instrument. Methods Forty-one in-depth semi-structured interviews were undertaken with older people (65 years and over) receiving community aged care services across three Australian states to explore quality of life characteristics of importance to them. The data were analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 40 publications
1
40
0
Order By: Relevance
“…walking stick or walking frame. This is because our Stage 1 in-depth qualitative interviews identified that older people who regularly use these devices considered themselves to be mobile [ 33 ]. This differentiates the QOL-ACC from other quality of life instruments developed with general adult populations, where a person using a mobility device could receive the lowest mobility score if they are not prompted to consider mobility aids when making their response.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…walking stick or walking frame. This is because our Stage 1 in-depth qualitative interviews identified that older people who regularly use these devices considered themselves to be mobile [ 33 ]. This differentiates the QOL-ACC from other quality of life instruments developed with general adult populations, where a person using a mobility device could receive the lowest mobility score if they are not prompted to consider mobility aids when making their response.…”
Section: Discussionmentioning
confidence: 99%
“…This methodological approach ensured that the final instrument is psychometrically robust as well as meaningful, relevant and acceptable to aged care consumers and providers. The QOL-ACC items were developed from qualitative interviews with older people receiving aged care services about what was important for them to feel like they had a good quality of life [ 33 ] and are therefore based on what is most relevant and meaningful to older people themselves. The face validity interviews removed items that older people saw as ambiguous or potentially sensitive, and the low levels of missing data suggest that items were acceptable to participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Suwa et al investigated and analyzed the views of Japan, Ireland, and Finland on the participation of robots in home care for the elderly by means of questionnaires [9]. Cleland et al conducted 41 in-depth, semistructured interviews with people over 65 years of age receiving community-based geriatric care in three Australian states to study the quality of community-based geriatric care [10].…”
Section: Literature Reviewmentioning
confidence: 99%